Parental Stress and Parental Self-Efficacy as Mediators of the Association Between Children's ADHD and Marital Satisfaction. Issue 5 (March 2019) - Ben-Naim, Shiri; Gill, Noam; Laslo-Roth, Roni; Einav, Michal
Parents of children with ADHD often experience low marital satisfaction, since the child's increased susceptibility to maladjustment can affect family dynamics as a whole.Objectives: To explore this association by examining parental stress and parental self-efficacy as two possible mediators.Method: Totally, 182 Israeli parents of children in the first to ninth grades (63 parents of children with ADHD and 119 without) completed parental self-efficacy, marital satisfaction, and parental stress questionnaires.Results: As expected, parents of children with ADHD reported higher parental stress, and lower self-efficacy and marital satisfaction than non-ADHD parents. The association between ADHD parents and marital satisfaction was fully explained by parental stress and self-efficacy, suggesting that personal characteristics and situation appraisal are tapped when facing strain and hardship.Conclusion: These findings provide a window of hope for an otherwise deterministic view of the ADHD-marital dissolution relationship and propose individual and familial interventions that may minimize these damaging effects.